2022
DOI: 10.1021/acs.energyfuels.2c01363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methanol Guests on Thermal Properties of NH4F-Doped THF Clathrate Hydrate

Abstract: Methanol is a widely known thermodynamic hydrate inhibitor, but recent studies revealed that an ammonium fluoride ion-pair doped into the host clathrate hydrate lattice can stabilize methanol in the hydrate cages. In this work, we examined THF + methanol clathrate formed from 27 mol % NH4F aqueous solution with powder X-ray diffraction (PXRD) and molecular dynamics (MD) simulations to investigate the effect of methanol guest molecules on the thermal properties of ammonium fluoride doped THF clathrate hydrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In a mini review, Uchida et al summarized the technologies for promoting the nucleation process in gas hydrate formation in addition to an account of recent studies on ultrafine bubbles to reduce induction time. Kim et al examined tetrahydrofuran (THF) + methanol clathrate formed from 27 mol % NH 4 F aqueous solution with PXRD and molecular dynamics simulations to investigate the effect of methanol guest molecules on the thermal properties of ammonium-fluoride-doped THF clathrate hydrates. Ovalle et al investigated hydrate propagation outside of the water boundary (halo) with different gas mixtures on a sapphire surface; the morphology was carefully studied; and using high-resolution imaging, it was concluded that the CO 2 -containing mixture produced the most halo.…”
Section: Fundamentalsmentioning
confidence: 99%
“…In a mini review, Uchida et al summarized the technologies for promoting the nucleation process in gas hydrate formation in addition to an account of recent studies on ultrafine bubbles to reduce induction time. Kim et al examined tetrahydrofuran (THF) + methanol clathrate formed from 27 mol % NH 4 F aqueous solution with PXRD and molecular dynamics simulations to investigate the effect of methanol guest molecules on the thermal properties of ammonium-fluoride-doped THF clathrate hydrates. Ovalle et al investigated hydrate propagation outside of the water boundary (halo) with different gas mixtures on a sapphire surface; the morphology was carefully studied; and using high-resolution imaging, it was concluded that the CO 2 -containing mixture produced the most halo.…”
Section: Fundamentalsmentioning
confidence: 99%